2000
DOI: 10.1080/003655100750019242
|View full text |Cite
|
Sign up to set email alerts
|

The use of human ultralente is limited by great intraindividual variability in overnight plasma insulin profiles

Abstract: Human ultralente insulin gives an insulin profile suitable for overnight substitution, but the great day-to-day variability limits its usefulness. It can be injected before dinner or at bedtime without any change in the insulin profile during the night.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…It is well established and widely accepted that basal human insulin preparations [Ultralente and neutral protamine Hagedorn (NPH) insulin] fall short of these desired properties [3,4]: they not only are suspensions that have to be thoroughly resuspended prior to injection, a requirement often ignored by many patients [5], but also show a pronounced peak effect, which can impose the risk of nocturnal hypoglycaemia. Furthermore, variability in the PD profile is high [6,7]– indeed, so high for Ultralente that it is hardly used any more [8]. The major disadvantage of NPH insulin, in addition to high variability, is its suboptimal duration of action: end of action is reported to occur after only 12–14 h [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established and widely accepted that basal human insulin preparations [Ultralente and neutral protamine Hagedorn (NPH) insulin] fall short of these desired properties [3,4]: they not only are suspensions that have to be thoroughly resuspended prior to injection, a requirement often ignored by many patients [5], but also show a pronounced peak effect, which can impose the risk of nocturnal hypoglycaemia. Furthermore, variability in the PD profile is high [6,7]– indeed, so high for Ultralente that it is hardly used any more [8]. The major disadvantage of NPH insulin, in addition to high variability, is its suboptimal duration of action: end of action is reported to occur after only 12–14 h [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…A high variability for Ultralente (Eli Lilly & Company, Indianapolis, IN, USA) was confirmed in a healthy volunteer study where the intra-subject CV was 67% for a 24-h insulin exposure [47]. This compared to significantly lower values of 19 and 15% for neutral protamine Hagedorn (NPH) insulin (Novo Nordisk, Bagsvaerd, Denmark) and insulin glargine, respectively [46]. For NPH insulin, intrasubject CV values of 24 and 28% were reported for maximum plasma concentration (C max ) and area under the concentration time-curve from time zero to infinity [AUC (0-∞) ], respectively, in a study of adults with T1D who were given four separate test injections [41].…”
Section: Measuring Variability In the Pharmacokinetic Profile Of Basamentioning
confidence: 89%
“…Those that have made this assessment suggest that the extent of variability is considerable. For example, a study of Ultralente reported an intra-subject CV of 50% in mean nocturnal plasma insulin concentration in patients with T1D [46]. A high variability for Ultralente (Eli Lilly & Company, Indianapolis, IN, USA) was confirmed in a healthy volunteer study where the intra-subject CV was 67% for a 24-h insulin exposure [47].…”
Section: Measuring Variability In the Pharmacokinetic Profile Of Basamentioning
confidence: 96%
“…The major disadvantages of Ultralente are day-to-day variability in absorption, inconsistent peak patterns, and erratic therapeutic outcomes. 52 Insulin glargine is an insulin analogue with structural molecular modifications [Gly A21 , Arg B31 , Arg B32 ] that result in a shift of the isoelectric point and reduced solubility at physiologic pH. The consequent formation of microprecipitates after subcutaneous injection delays its absorption into the systemic circulation.…”
Section: Insulinmentioning
confidence: 99%